Payang fiber mould project / Mohammad Yushaiman Habib Muhd Yusoff ... [et al.] - Muhd Yusoff, Mohammad Yushaiman Habib; Wan Zakaria, Wan Mohamad Fahmi; Lokman @ Nejib, Muhammad Arash Mifzal; Izaudin, Muhammad Hasif Fitri; Muhammad Hilmi, Ahmad Haiqal Fikri (2021)
The overview of the making mould of the Perahu Payang is, our group start with make a brainstorming. Then, our group make the detail design from the design of perahu payang that we get from the lecture. This process is to make sure the mould is precise. After that, our group proceed with making the design of the mould using the Rhino 6 software. Next, we make the make the illustration of the cutting process of the mould using the Powermill software.